Performance Measurement Systems: Strategic Lever for Value Creation - Hammouch, Hind (iRASD Journal of Management, 2024)
In the Moroccan context, performance measurement is vital to organizations at all levels. Its importance is increasingly recognized as a crucial area of academic research. Despite sometimes ambiguous definitions, performance remains a central concern for economic players. Accurate measurement is essential for continuous improvement and the implementation of appropriate information systems. Therefore, the right choice of performance measurement methods is essential to the success of decision-making processes. In a highly competitive economic environment, organizations are seeking to maximize their profits on a sustainable basis. To achieve this, they need to be equipped with the necessary tools. It is, therefore, crucial to improve the relevance of performance measurement practices at all levels of their operations. By optimizing these practices, organizations can effectively monitor and evaluate their performance, identify areas requiring improvement, and adjust their strategies accordingly. This strengthens decision-making and supports sustainable organizational growth.